THE ROLE OF EDUCATORS MADRASAH DINIYAH TAKMILIYAH AWALIYAH IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN MADRASAH DINIYAH TAKMILIYAH AWALIYAH AR-RAHMAH RAHUNING, ASAHAN DISTRICT - Ali Imran Sinaga; Mardianto Mardianto (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The purpose of this research is to describe the role of Madrasah Diniyah Takmiliyah Educators in Improving the Quality of Islamic Religious Education, and to find out the process of improving the quality of Islamic Religious Education at Madrasah Diniyah Takmiliyah Ar - Rahmah and what are the obstacles and efforts to improve the quality of Islamic Education. This study uses a qualitative research method, which is a study that intends to understand the phenomenon of what is experienced by the research subject, for example behavior, perception, motivation, action and others, holistically and by way of description in the form of words and language, at a time. special contexts that are natural and by utilizing various natural methods, and in natural field situations as they are without manipulation. The results of this study show that: (1) The role of madrasah diniyah takmiliyah Awaliyah Ar-Rahmah in improving the quality of Islamic religious education (2) Forms of cooperation between Madrasah diniyah takmiliyah Awaliyah Ar-Rahmah and parents of students (3) the process of improving the quality of Islamic religious education in Madrasah Diniyah Takmiliyah Awaliyah Ar-Rahmah (4) obstacles and efforts in improving the quality of Islamic religious education.